Transition metal-free 3 + 3 annulation of cyclopropanols with β-enamine esters to assemble nicotinate derivatives - Zhan, Jun-Long; Zhu, Lin; Bai, Jia-Nan; Liu, Jian-Bo; Zhang, Shi-Han; Xie, Yao-Qiang; Hu, Bo-Mei; Wang, Yang; Han, Wen-Jun (Organic & biomolecular chemistry, 2023)
A metal-free and efficient approach for the synthesis of structurally important nicotinates through 4-HO-TEMPO-mediated [3 + 3] annulation of cyclopropanols with β-enamine esters is presented. This protocol features high atom efficiency, green waste, simple operation and broad substrate scope. Moreover, the experiments of gram-scale synthesis and recovery of oxidants make this strategy more sustainable and practical.A metal-free and efficient approach for the synthesis of structurally important nicotinates through 4-HO-TEMPO-mediated [3 + 3] annulation of cyclopropanols with β-enamine esters is presented. This protocol features high atom efficiency, green waste, simple operation and broad substrate scope. Moreover, the experiments of gram-scale synthesis and recovery of oxidants make this strategy more sustainable and practical.